Label-free detection of pH based on the i-motif using an aggregation-caused quenching strategy. Issue 95 (7th October 2015) - Fu, Boshi; Huang, Jinguo; Bai, Dongsheng; Xie, Yalun; Wang, Yang; Wang, Shaoru; Zhou, Xiang
Abstract : A label-free and biocompatible pH sensor system based on the aggregation-caused quenching (ACQ) probe has been reported herein. Abstract : A label-free and biocompatible pH sensor system based on the aggregation-caused quenching (ACQ) probe has been reported herein. The DNA i-motif, a kind of pH-triggered structure, affects the aggregation of PTCDI derivatives by structural switch that would provide significant fluorescence signals responding to the different pH values. Our method not only shows sensitive and reversible response to pH changes, but also could expand the detection range by allosteric control of the DNA i-motif.